Sodium Selenate Treatment Using a Combination of Seed Priming and Foliar Spray Alleviates Salinity Stress in Rice - Subramanyam, Kondeti; Du Laing, Gijs; Van Damme, Els J. M. (Frontiers in Plant Science, 2019)
Soil salinity is one of the important abiotic stress factors that affect rice productivity and quality. Research with several dicotyledonous plants indicated that the detrimental effects associated with salinity stress can (partly) be overcome by the external application of antioxidative substances. For instance, sodium selenate (Na2SeO4) significantly improved the growth and productivity of several crops under various abiotic stress conditions. At present there is no report describing the impact of Na2SeO4 on salinity stressed cereals such as rice. Rice cultivation is threatened by increasing salinity stress, and in future this problem will further be aggravated by global warming and sea level rise, impacting coastal areas. The current study reports on the effect of Na2SeO4 in alleviating salinity stress in rice plants. The optimal concentration of Na2SeO4 and the most efficient mode of selenium application were investigated. Selenium, sodium and potassium contents in leaves were determined. Antioxidant enzyme activities as well as proline, hydrogen peroxide, and malondialdehyde concentrations were analyzed. In addition, the transcript levels for OsNHX1, an important Na+/H+ antiporter, were quantified. Treatment of 2-week-old rice plants under 150 mM NaCl stress with 6 mg l–1 Na2SeO4 improved the total biomass. A significantly higher biomass was observed for the plants that received Na2SeO4 by a combination of seed priming and foliar spray compared to the individual treatments. The Na2SeO4 application enhanced the activity of antioxidant enzymes (SOD, APX, CAT and GSH-Px), increased the proline content, and reduced hydrogen peroxide and malondialdehyde concentrations in plants under NaCl stress. These biochemical changes were accompanied by increased transcript levels for OsNHX1 resulting in a higher K+/Na+ ratio in the rice plants under NaCl stress. The results suggest that Na2SeO4 treatment alleviates the adverse effect of salinity on rice plant growth through enhancing the antioxidant defense system and increase of OsNHX1 transcript levels.